Perilaku Perlawanan dan Pembantahan Siswa Terhadap Guru dalam Proses Pembelajaran (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This study examines students' resistance and arguing behavior towards teachers in the learning process. The purpose is to identify the causative factors and their impact on the effectiveness of learning. The results of the study show that the disputing behavior can be caused by a lack of motivation, disagreement with teaching methods, or personal problems that affect the emotional state of students. This behavior can disrupt the focus of other students and prevent the teacher from delivering the material effectively. Therefore, good cooperation between teachers and students is needed to create a conducive learning atmosphere. An approach that emphasizes awareness, empathy and responsibility for students is important in overcoming this problem. This research provides valuable insights for schools, teachers, and parents in understanding and addressing oppositional behavior, so as to improve the effectiveness of the learning process.